2023
DOI: 10.1097/j.pbj.0000000000000199
|View full text |Cite
|
Sign up to set email alerts
|

Candidates selection for oocyte donation in a public gamete bank—Predictive value of the anti-Müllerian hormone

Abstract: Background:Infertility treatments with oocyte donation are becoming frequent. Recruitment of oocyte donors is a demanding and costly process and therefore of crucial importance. The selection of the oocyte donors undergoes a rigorous evaluation process of the candidates with routine measurement of the anti-Müllerian hormone (AMH) levels (ovarian reserve test). Our aim was to assess whether AMH levels could act as a good marker as tool to select the donor candidates and correlate them with the ovarian response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…Serum AMH levels of them were similar compared to those of healthy patients in other populations. 42,43 Furthermore, our multiple regression analysis showed that the serum AMH level is independently affected by the presence of PCOS and by age, in agreement with our previous report. 41 The number of follicles in every growing stage tends to be greater in women with PCOS than in healthy women, [44][45][46] which is remarkable in the small antral and pre-antral follicle stages.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Serum AMH levels of them were similar compared to those of healthy patients in other populations. 42,43 Furthermore, our multiple regression analysis showed that the serum AMH level is independently affected by the presence of PCOS and by age, in agreement with our previous report. 41 The number of follicles in every growing stage tends to be greater in women with PCOS than in healthy women, [44][45][46] which is remarkable in the small antral and pre-antral follicle stages.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the control group consisted of patients that initiated ART in the absence of ovulatory disorders. Serum AMH levels of them were similar compared to those of healthy patients in other populations 42,43 . Furthermore, our multiple regression analysis showed that the serum AMH level is independently affected by the presence of PCOS and by age, in agreement with our previous report 41 .…”
Section: Discussionsupporting
confidence: 91%
“…The current study lays the groundwork to validate AMH levels as a prognostic factor for pregnancy after IVF in women with PCOS, as AMH levels below 3.7 ng/mL were found to be associated with better pregnancy outcomes. This range of AMH values (under 3.5 ng/mL) is found among healthy women and has been linked with good ovarian response to stimulation [27][28][29]. Although this seems to be transversal to PCOS, the relationship between baseline AMH levels and pregnancy outcomes in women with PCOS may not be as straightforward and requires further investigation.…”
Section: Discussionmentioning
confidence: 93%
“…(2021 ) predicted a cutoff level of 0.93 ng/mL. According to Vale-Fernandes et al (2023) , a threshold value of AMH = 3.2 ng/mL predictive of the retrieval <12 oocytes (areas under the curve, 0.7364; 95% confidence interval: 0.529-0.944) was identified by receiver operating characteristic curve. Using this cutoff, the normal response (12 oocytes) was predicted with a sensitivity of 77% and a specificity of 60%.…”
Section: Discussionmentioning
confidence: 99%